Final Protocol and Statistical Analysis Plan for the SNAP Trial - a randomised, double-blind, placebo-controlled trial of nicotine replacement therapy in pregnancy - Coleman, Tim; Cooper, Sue; Thornton, Jim; Britton, John; Lewis, Sarah; Watts, Kim; Coughtrie, Michael; Mannion, Clare; Marlow, Neil; Godfrey, Christine; Grainge, Matthew J. (None, 2012)
This NIHR HTA-funded smoking, nicotine and pregnancy (SNAP) trial investigated whether or not nicotine replacement therapy (NRT) is effective, cost-effective and safe when used for smoking cessation by pregnant women. We randomised 1050 women who were between 12 and 24 weeks pregnant as they attended hospital for ante-natal ultrasound scans. Women received either nicotine or placebo transdermal patches with behavioural support. The primary outcome measure was biochemically-validated, self-reported, prolonged and total abstinence from smoking between a quit date (defined before randomisation and set within 2 weeks of this) and delivery. At 6 months after childbirth self-reported maternal smoking status was ascertained and 2 years after childbirth, self-reported maternal smoking status and the behaviour, cognitive development and respiratory symptoms of children born in the trial were compared in both groups. This repository contains the final approved version of the protocol plus the statistical analysis plan (SAP) for both outcomes at delivery and following the 2 year follow up period after birth.